The Development of Islamic Education Curriculum from the Quranic Perspective - Manal Hendawi; Ghadah Al Murshidi; Asrori Asrori; Muhammad Fazlurrahman Hadi; Miftachul Huda; Terence Lovat (CV. Zamron Pressindo, 2024)
Research Objective– This study aims to analyze the development of the Islamic education curriculum from the Quranic perspective, focusing on the values of Tawhid as the philosophical foundation, content, methods, and evaluation of the curriculum. Methodology– This research employs a library research method, using a thematic analysis approach on Quranic verses, classical Islamic literature, and modern academic sources. Data were categorized into theological, cosmological, and anthropo-sociological aspects to formulate a curriculum development framework based on Tawhid values. Findings– The study findings indicate that Tawhid values play a central role as a holistic foundation for designing a curriculum that emphasizes harmonious relationships between humans and God, humans with one another, and humans with the environment. The curriculum includes the integration of modern science and Islamic values, along with the adaptation to global challenges such as technological advancements, social value shifts, and environmental crises. Research Implications/Limitations– This study highlights the importance of an Islamic education curriculum that is adaptive to technology and global issues, while maintaining Tawhid principles. However, this study is limited to theoretical analysis and requires further empirical validation for practical application. Originality/Value– This research provides an original contribution by developing a Tawhid-based Islamic education framework that is relevant to modern challenges. This approach integrates spiritual, intellectual, and social values to create harmony in all aspects of life.